KONSTRUKSI DAKWAH ISLAM MODERAT NAHDLATUL ULAMA DI MEDIA SOSIAL NU ONLINE PADA ERA SOCIETY 5.0 - Muhammad Alfan Taufiqi (Jurnal Komunikasi, 2025)
The rapid development of digital communication technology has significantly transformed Islamic da’wah practices in terms of media usage, methods, and interaction patterns between preachers and audiences. Social media has evolved not only as a channel for information dissemination but also as a space for constructing religious meanings and contesting Islamic discourses. This article aims to examine the optimization of Nahdlatul Ulama’s da’wah through NU Online social media in responding to the challenges of the Society 5.0 era. This study employs a qualitative descriptive approach using literature review and conceptual analysis of NU Online’s da’wah content. The findings reveal that NU Online constructs moderate Islamic da’wah through contextual, rational, and inclusive narratives by integrating normative Islamic sources with scientific perspectives. In the context of Society 5.0, NU Online functions as a digital da’wah medium that seeks to balance technological advancement with humanistic values. Optimizing digital da’wah requires media innovation, audience sensitivity, and effective message management to prevent distortion of religious meanings